Silver nanoparticle based alcohol sensor manufacturing training for detection of halal drinks - Chresiani Destianita Yoedistira; Muhammad Hilmi Afthoni; Rokiy Alfanaar (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Nowadays, halal drinks are one of the sectors that get the attention of various parties. Alcohol in beverages is important in determining the halalness of a beverage. Halal detection can be done using chemical sensors. In the Pharmacy Department, knowledge of analysis using sensors is rare. Therefore, this community service program was carried out to introduce qualitative methods of quick and simple alcohol analysis. The participants are students of the Pharmacy Department of STIKES Anwar Medika in Sidoarjo City. Participants are communities engaged in the health sector who have an interest in halal and how to make sensors for halal testing. This program is implemented by making a video on how to make a chemical sensor for alcohol detection. The chemical sensor is a paper-immobilized colloidal silver-based chemical sensor that is easy to apply in various conditions. Based on the results of the color change produced on the filter paper, from green to bluish which indicates that the food or beverage sample contains alcohol. Based on the questionnaire, participants expressed satisfaction with the increase in knowledge about additional tools that are easy and fast to detect alcohol.